Analisis Faktor Penyebab Keterlambatan Proyek “XYZ” - Dwiantoro, Deny; Yoansa, Acep Yosep; Indrayana, Desiderius Viby; Mentari, Sekar; Widyatami, Filki Suri (Jurnal Talenta Sipil, 2024)
A project tends to experience delays if planning and control are not carried out properly. Various things can happen in a construction project that can cause an increase in processing time so that project completion is delayed. The purpose of this research is to identify and classify the factors that cause delays in the "XYZ" project. This data processing uses the help of the SPSS (Statistical Product and Service Solution) computer program version 23.00. Data analysis techniques using validity, reliability and factor analysis techniques. The results of this study obtained 3 new factors from the extraction results of factor analysis, namely: Lack of Expertise and Slow Material Mobilization (Xb1), Lack of Planning and Inadequate Quality of Workforce (Xb2), Changes in Scope and Work Documents (Xb3).